It's About Time: Effects of the Affordable Care Act Dependent Coverage Mandate on Time Use - Gregory Colman; Dhaval M. Dave (Institute for the Study of Labor (IZA), 2016)
One of the main purposes of recent healthcare reform (Patient Protection and Affordable Care Act - ACA) in the U.S. is to enable Americans to make more productive use of their time. We examine how the ACA's dependent care coverage mandate (DCM) affected young adults' time allocation. Based on more accurate measures from the American Time Use Surveys and difference-in-difference methods, we first confirm that the DCM reduced labor supply. The question then arises, what have these adults done with the extra time? We provide some of the first evidence on this issue. Estimates suggest that the DCM has reduced job-lock, as well as the duration of the average doctor's visit, including time spent waiting for as well as receiving medical care, among persons ages 19-25. The latter effect is consistent with substitution from hospital ER utilization to more routine physician care. The extra time has gone into socializing, and to a lesser extent, into educational activities and job search. A related question is whether these changes have made young adults better off. We find that the availability of insurance and change in work time appear to have increased their subjective well-being, enabling them to spend time on activities they view as more meaningful than those they did before insurance became available.
Keywords: I1; J2; H0; 330; health insurance; labor supply; time use; leisure; medical care; Affordable Care Act; waiting time; well-being; work